2013
DOI: 10.1159/000350554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gestational Age on Neonatal Hearing Screening in Vaginally-Born Late-Preterm and Early-Term Infants

Abstract: Background: Late-preterm and early-term (LP-ET) infants, defined herein as 35⁰-376 weeks' gestation, often fail on 1st otoacoustic emissions (OAE) test. Hypothesis: LP-ET infants fail more than term infants (38⁰-42 weeks' gestation) on the 1st OAE test. Aim: To evaluate the effect of gestational age on the 1st OAE test. Methods: We studied 1,572 vaginally-delivered (VD) infants ≥35 weeks' gestation (1.1.2011-30.9.2011). Perinatal and neonatal variables and results of OAE tests were recorded. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In a study that evaluated the effect of gestational age in the baby hearing test carried out with Otoacoustic Emissions (OAE), the authors (36) compared late preterm infants to full-term infants and found it was two times more necessary to repeat listening tests in the first group, because these children presented higher failure rates in the first EOA performed up to 42 hours after birth. As there was no significance in failure rates after 42 hours in both groups, they concluded that the results in late preterm infants are related to late maturation of the auditory system after birth, in agreement with one of the studies selected (34) , in which it was verified that maturation of the auditory system has a greater influence than factors such as weight at birth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study that evaluated the effect of gestational age in the baby hearing test carried out with Otoacoustic Emissions (OAE), the authors (36) compared late preterm infants to full-term infants and found it was two times more necessary to repeat listening tests in the first group, because these children presented higher failure rates in the first EOA performed up to 42 hours after birth. As there was no significance in failure rates after 42 hours in both groups, they concluded that the results in late preterm infants are related to late maturation of the auditory system after birth, in agreement with one of the studies selected (34) , in which it was verified that maturation of the auditory system has a greater influence than factors such as weight at birth.…”
Section: Resultsmentioning
confidence: 99%
“…Considering hearing conditions, it is known that auditory monitoring of premature children is also extremely important, not only to avoid or remedy hearing problems, but also to minimize their effects on language acquisition. Some research results suggest that prematurity affects the maturation process of the central auditory nervous system, including maturation of the auditory pathway, as well as the weight at birth factor, which may negatively impact the process of language acquisition and learning (33)(34)(35)(36) . In line with these works, another study (47) observed a statistically significant association among maturation of the auditory pathway, cognition and communication (at 12 months) and receptive language (at 24 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Late-preterm and early-term (35–37 6 weeks' gestation) infants born vaginally have twice the OAE failure rate within 42 hours after birth compared with term infants, and it is therefore recommended that the first OAE test be performed 42 hours after birth. 58 The OAEs of the tested ear can be suppressed by acoustic stimulation of the contralateral ear, and this efferent system is not activated at low noise levels. OAE tests are usually performed in hospitals or clinics, with ambient noise levels as high as 60 to 70 dB sound pressure levels (SPL), and thus the OAEs in the tested ear may be affected by noise stimulation in the contralateral ear.…”
Section: Neonatal Hearing Loss–related Screeningmentioning
confidence: 96%
“…91 For preterm infants with transvaginal delivery, the first OAE screening is recommended 42 hours after birth. 58 For preterm infants with a gestational age of <28 weeks, the developmental maturation of hearing potential appears prior to the corrected gestational age of 80 weeks. Hearing levels in preterm infants may improve over time, so before cochlear implantation, the delayed auditory maturation and initial hearing level of infants should take into account.…”
Section: Updated Hearing Screening Strategiesmentioning
confidence: 99%